The influence of Herzberg’s motivator factor on employees’ organizational citizenship behaviour / Noorlaila Yunus and Cairul Azwa Azimi - Yunus, Noorlaila; Azimi, Cairul Azwa (Universiti Teknologi MARA Cawangan Selangor, 2016)
Organizational Citizenship Behaviour (OCB) has been widely studied across the boarders especially in the western countries. This workplace voluntary behaviour is associated with many predictors that may bring whether major, minor or negative influence towards the engagement of employees’ OCB. Basically, this study is focusing on motivation as the predictor or independent variable that influence employees’ engagement on the OCB (altruism, conscientiousness, courtesy, civic virtue and sportsmanship) behaviour. Herzberg’s motivator factor (achievement, advancement, recognition and growth) has been chosen as the independent variable. A total of 150 questionnaires were distributed conveniently to respondents. With 125 questionnaires returned, researcher was able to analyze the data based on the research questions and hypotheses developed. The findings showed moderate and weak, significant relationship between the variable excluding the relationship between independent variable and civic virtue and sportsmanship. Thus, Herzberg’s motivator factor was not a predictor to civic virtue and sportsmanship behaviour. However for the strongest predictor; achievement, growth and growth are strongly predicts the altruism, conscientiousness and courtesy behaviour respectively. However, with the absence of relationship between independent variable and civic virtue as well as sportsmanship, therefore the strongest predictor cannot be determined as the value recorded was below the criterion.